2019
DOI: 10.1038/s41598-019-51660-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered temporal sensitivity in obesity is linked to pro-inflammatory state

Abstract: Temporal sensitivity to multisensory stimuli has been shown to be reduced in obesity. We sought to investigate the possible role of the pro-inflammatory state on such alteration, considering the effect of the expression of markers, such as leptin and IL6, which are notably high in obesity. The performance of 15 male individuals affected by obesity and 15 normal-weight males was compared using two audiovisual temporal tasks, namely simultaneity judgment and temporal order judgment. Analyses of serum levels of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
1
5
0
1
Order By: Relevance
“…Nevertheless, to have conclusive remarks, both components should be investigated in the same sample. Furthermore, as previous evidence pinpointed that individuals affected by obesity show altered temporal sensitivity (Scarpina et al, 2019a(Scarpina et al, , 2019bTagini et al, 2020b), future studies could investigate whether the alteration of the SA effect observed here is linked to this impairment, by including different temporal delays between the self-and other-generated action and the stimulus delivery.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Nevertheless, to have conclusive remarks, both components should be investigated in the same sample. Furthermore, as previous evidence pinpointed that individuals affected by obesity show altered temporal sensitivity (Scarpina et al, 2019a(Scarpina et al, , 2019bTagini et al, 2020b), future studies could investigate whether the alteration of the SA effect observed here is linked to this impairment, by including different temporal delays between the self-and other-generated action and the stimulus delivery.…”
Section: Discussionmentioning
confidence: 85%
“…Eighteen participants affected by obesity were recruited during the first week of a diagnostic recovery in the IRCCS Istituto Auxologico Italiano, Ospedale San Giuseppe (Piancavallo, Italy). In line with previous studies (Scarpina et al, 2016(Scarpina et al, , 2019a(Scarpina et al, , 2019bTagini et al, 2020aTagini et al, , 2020bTagini et al, , 2021a, only participants with a body mass index (i.e., BMI) over the value of 30 (i.e., indicating obesity, World Health Organization, 2000) were included. We excluded individuals with any neurological symptoms/signs, especially of neuropathic pain, according to the clinical assessment.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Є дані про спільність генетичних детермінант СОАС та ожиріння. У дослідженнях показали, що поліморфізми рецептора лептину -медіатора енергетичного гомеостазу та регуляції маси тіла, IL6, -значною мірою пов'язані як з CОАС, так і з ожирінням [25].…”
Section: полтавський державний медичний університет українаunclassified
“…Indeed, a defective (i.e., enlarged) multisensory TBW seems to play a role in the perceptual and cognitive weaknesses featuring some neurological (e.g., Bolognini et al 2013 , 2016 ; Maccora et al 2020 ) and neuropsychiatric/neurodevelopmental diseases, such as autism, dyslexia, schizophrenia (Wallace and Stevenson 2014 ), as well as in mild cognitive impairment (Chan et al 2015 ). On a broader perspective, multisensory integration deficits have been revealed in diseases affecting brain functioning and they have been proposed to be associated, and in some cases could be even responsible of, the clinical symptomology (e.g., obesity, acquired-brain injury, migraine and Parkinson’s and Alzheimer diseases; Bolognini et al 2013 ; Brighina et al 2015 ; Scarpina et al 2016 , 2019 ; Tagini et al 2020 ; Van der Stoep et al 2019 ; Yakubovich et al 2020 ; Wu et al 2012 ). This because many crucial cognitive and perceptual functions depend on the ability to process and integrate multisensory information.…”
Section: Introductionmentioning
confidence: 99%